2014
DOI: 10.3389/fnhum.2014.00290
|View full text |Cite
|
Sign up to set email alerts
|

Motor imagery modulation of body sway is task-dependent and relies on imagery ability

Abstract: In this study we investigate to what extent the effects of motor imagery on postural sway are constrained by movement features and the subject's imagery ability. Twenty-three subjects were asked to imagine three movements using the kinesthetic modality: rising on tiptoes, whole-body forward reaching, and whole-body lateral reaching. After each task, subjects reported the level of imagery vividness and were subsequently grouped into a HIGH group (scores ≥3, “moderately intense” imagery) or a LOW group (scores ≤… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 62 publications
(108 reference statements)
3
20
0
1
Order By: Relevance
“…Fear has shown influence on the ability to perform gait MI [41]. Studies have shown that kinesthetic MI presents a modulation effect on orthostatic postural control [7][8][9], depending on the vividness of the imagined movement [10], corroborating our results, since the participants also presented high levels of vividness (KVIQ). The present study also showed that the FoF during the tasks of kinesthetic MI (cervical flexion and inclination) is able to modulate the CoP variables, increasing their oscillation, which indicates greater postural imbalance (Figure 2A,B).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Fear has shown influence on the ability to perform gait MI [41]. Studies have shown that kinesthetic MI presents a modulation effect on orthostatic postural control [7][8][9], depending on the vividness of the imagined movement [10], corroborating our results, since the participants also presented high levels of vividness (KVIQ). The present study also showed that the FoF during the tasks of kinesthetic MI (cervical flexion and inclination) is able to modulate the CoP variables, increasing their oscillation, which indicates greater postural imbalance (Figure 2A,B).…”
Section: Discussionsupporting
confidence: 89%
“…For example, when an individual performs and imagines walking at a fixed distance, the time spent is similar, with no statistical difference [40]. Similarly, the number of repetitions of the same executed and imagined task in a "fixed time window" also presents no statistical difference [7,9,10]. Although the sample (n = 20) also has shown similarity between the execution and imagination of the tasks (cervical flexion and inclination) when comparing the number of repetitions (principle of isochronia), this same similarity was not observed when comparing the sensation of FoF between execution and imagination, indicating that the MI induces a greater modulation in the sensation of FoF in relation to the execution of the same tasks (see Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 2 , 9 So far, the work done with CRPS using the MI has not taken into account these two types of strategies (Supplementary Tables S1-3) and it may exist different effects between them. For example, it has been shown that the MI kinesthetic has greater sway center of pressure (CoP) compared with the visual MI in different tasks 35-37 and this effect has been correlated with the intensity of the imagined movement, 38 which is another point that has not been explored in studies with CRPS-1. Therefore, it can be expected that MI strategies (visual and kinesthetic) may also have different effects on pain perception in the CRPS-1 reorganization.…”
Section: Methodsmentioning
confidence: 99%